2015
DOI: 10.1186/s40172-014-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

College major peer effects and attrition from the sciences

Abstract: This paper examines how peer quality within distinct college majors affects graduation rates and major persistence. To mitigate the selection problem, we control for school-specific fixed effects, as well as very flexible applicationadmissions pattern fixed effects. Non-science peer quality appears to have a positive effect on both the likelihood that a student chooses a science major and on his or her cumulative GPA. Conversely, students who attend campuses with stronger peers in the sciences are less likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…Webber (2012) reports that college completion is affected by a college's expenditures on student services and instruction, while Price (2010) finds that black students are more likely to persist in STEM majors if they have a course taught by a black professor. Luppino and Sander (2015) and Arcidiacono et al (2013) provide evidence of peer competition effects in the University of California system; they find that attending a more competitive campus makes a student of a given quality less likely to earn a degree in the sciences. In addition to these empirical findings, there are other possible reasons why the probability of earning a STEM major might differ across colleges.…”
Section: Change In Enrollment Patternsmentioning
confidence: 99%
“…Webber (2012) reports that college completion is affected by a college's expenditures on student services and instruction, while Price (2010) finds that black students are more likely to persist in STEM majors if they have a course taught by a black professor. Luppino and Sander (2015) and Arcidiacono et al (2013) provide evidence of peer competition effects in the University of California system; they find that attending a more competitive campus makes a student of a given quality less likely to earn a degree in the sciences. In addition to these empirical findings, there are other possible reasons why the probability of earning a STEM major might differ across colleges.…”
Section: Change In Enrollment Patternsmentioning
confidence: 99%
“…For non-science majors, they found that peer quality has a positive effect on cumulative GPA and whether a student chooses a science major. Students who attend more selective schools that have stronger peers in the sciences are less likely to graduate with a science degree (Luppino and Sander, 2015).…”
Section: Why Do Students Switch Majors?mentioning
confidence: 99%
“…Minorities in this situation tend to persist in the selected science major regardless of peer quality. Due to this behavior, the minority students suffer substantially in more competitive programs in terms of GPA and the probability of receiving their degree (Luppino and Sander, 2015).…”
Section: Race or Ethnicitymentioning
confidence: 99%
“…Recent research shows that having higher ability STEM peers actually decreases the probability of graduating with a STEM major (Fischer ; Luppino and Sander ). Luppino and Sander () analyze a rich dataset covering all students at the eight University of California campuses and find that students who attend campuses with higher ability peers in the STEM fields are less likely to graduate with a STEM degree.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent research shows that having higher ability STEM peers actually decreases the probability of graduating with a STEM major (Fischer ; Luppino and Sander ). Luppino and Sander () analyze a rich dataset covering all students at the eight University of California campuses and find that students who attend campuses with higher ability peers in the STEM fields are less likely to graduate with a STEM degree. Similarly, Fischer () finds that, for women, a higher percentage of high ability peers in an introductory STEM course decreases the probability of persistence in a STEM field (she finds no discernable peer effect on men).…”
Section: Theoretical Frameworkmentioning
confidence: 99%